2015
DOI: 10.1007/s10900-015-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Intervention on Cervical Cancer Prevention and Screening in Hispanic Women

Abstract: To evaluate the effect of an educational intervention on four domains of health care utilization and cervical cancer prevention and screening in a Hispanic population. Data collected from a survey were used to design education strategies focused on four domains of interest. A second survey was conducted to measure the impact of the intervention. Following the intervention, respondents were more likely to have any knowledge of human papillomavirus (HPV). Respondents living in the United States (US) for <5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…One pamphlet or educational material may not be sufficient, and education may need to be delivered over a longer period of time, as opposed to a one-time exposure. Results from this study make it clear that effective cervical cancer screening interventions are needed to not only increase screening uptake, 17 but to increase awareness and knowledge, address perceptions, and promote adherence to screening guidelines, 18 and additional research is needed to understand the essential core components of educational interventions 19,20 targeting screening attitudes and beliefs among low-income and medically underserved women.…”
Section: Discussionmentioning
confidence: 99%
“…One pamphlet or educational material may not be sufficient, and education may need to be delivered over a longer period of time, as opposed to a one-time exposure. Results from this study make it clear that effective cervical cancer screening interventions are needed to not only increase screening uptake, 17 but to increase awareness and knowledge, address perceptions, and promote adherence to screening guidelines, 18 and additional research is needed to understand the essential core components of educational interventions 19,20 targeting screening attitudes and beliefs among low-income and medically underserved women.…”
Section: Discussionmentioning
confidence: 99%
“…By engaging the target community, they were able to significantly increase middle and high school students’ interest in vaccination through education ( 52 ). A study targeting Hispanic women first administered a survey to ensure the educational material was tailored toward the target population’s baseline knowledge and was able to demonstrate significant increase in intention to vaccinate ( 53 ). While these two studies were successful in increasing interest in vaccination and willingness to vaccinate, other attempts have been less successful.…”
Section: Interventions To Improve Delivery Of the Hpv Vaccinementioning
confidence: 99%
“…Public health research suggests that awareness and knowledge of HPV are important to vaccine acceptance and uptake (Beavis & Levinson, 2016; Foley et al, 2015; Galbraith et al, 2016; Kessels et al, 2012). However, systematic investigation has documented highly variable levels of knowledge and awareness (Beshers, Murphy, Fix, & Mahoney, 2015; Blake et al, 2015; Daley et al, 2011; Pierre et al, 2014; Reimer, Schommer, Houlihan, & Gerrard, 2014), and recently published research found that only 68% of respondents from a nationally representative sample of U.S. adults had heard of HPV and the HPV vaccine (Blake et al, 2015).…”
mentioning
confidence: 99%